Archvillain - Lyga, Barry (New York : Scholastic Press, 2010)
Twelve-year-old Kyle Camden develops greater mental agility and superpowers during a plasma storm that also brings Mighty Mike, an alien, to the town of Bouring, but while each does what he thinks is best, Kyle is labeled a villain and Mike a hero.
Wilson's Children, September 2011
Wilson's Junior High School, September 2011
School Library Journal, October 2010
Publisher's Weekly, September 2010
Booklist, September 2010
Horn Book, May 2011
Keywords: Superheroes -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Good and evil -- Juvenile fiction; Superheroes -- Fiction; Extraterrestrial beings -- Fiction; Good and evil -- Fiction; Science fiction; Superheroes -- Fiction; Extraterrestrial beings -- Fiction; Good and evil -- Fiction; Science fiction; Science fiction